Effect of osmolytes on the binding of EGR1 transcription factor to DNA. Issue 2 (February 2015) - Mikles, David C.; Bhat, Vikas; Schuchardt, Brett J.; McDonald, Caleb B.; Farooq, Amjad
ABSTRACT Osmolytes play a key role in maintaining protein stability and mediating macromolecular interactions within the intracellular environment of the cell. Herein, we show that osmolytes such as glycerol, sucrose, and polyethylene glycol 400 (PEG400) mitigate the binding of early growth response (protein) 1 (EGR1) transcription factor to DNA in a differential manner. Thus, while physiological concentrations of glycerol only moderately reduce the binding affinity, addition of sucrose and PEG400 is concomitant with a loss in the binding affinity by an order of magnitude. This salient observation suggests that EGR1 is most likely subject to conformational equilibrium and that the osmolytes exert their effect via favorable interactions with the unliganded conformation. Consistent with this notion, our analysis reveals that while EGR1 displays rather high structural stability in complex with DNA, the unliganded conformation becomes significantly destabilized in solution. In particular, while liganded EGR1 adopts a well‐defined arc‐like architecture, the unliganded protein samples a comparatively large conformational space between two distinct states that periodically interconvert between an elongated rod‐like shape and an arc‐like conformation on a submicrosecond time scale. Consequently, the ability of osmolytes to favorably interact with the unliganded conformation so as to stabilize it could account for the negative effect of osmotic stress on EGR1–DNA interaction observed here. Taken together, our study sheds new light on the role of osmolytes in modulating a key protein–DNA interaction. © 2014 Wiley Periodicals, Inc. Biopolymers 103: 74–87, 2015.